WORKING CAPITAL EFFICIENCY TOWARDS PROFITABILITY IN THE SAMI JAYA CREDIT COOPERATIVE IN KUPANG - Marince A. Rata; Paulina Yuritha Amtiran (STIE Muhammadiyah Jakarta, 2021)
Credit cooperatives are business service institutions formed by a group of people who voluntarily save their money together so that a certain amount of capital is formed, which is then lent between them at a reasonable interest rate and in an easy way, whose management applies cooperative principles. This study aims to determine the working capital that has been managed efficiently, to determine the effect of working capital on profitability, and to determine the factors that affect the efficiency of working capital in the Sami Jaya Credit Cooperative in Kupang. The research period used is the period 2015 - 2019. This research is a quantitative descriptive study. The data used in this research are working capital turnover, cash turnover, accounts receivable turnover, NPM, ROE, and ROA. The results of this study indicate that the working capital of the Sami Jaya credit cooperative is less efficient because each year the working capital does not reach the standard measurement so that its profitability is also inefficient.